Endodontic cements: morphological analysis carried out immediately and after a six-month storage, using atomic force microscopy (Pesquisa Odontológica Brasileira, 2000)
The aim of this study was to analyze the high resolution morphological characteristics of Sealapex, Apexit, Sealer 26 (calcium hydroxide cements) and Ketac Endo (glass ionomer cement), using atomic force microscopy (AFM), immediately after root canal obturation and six months after it, keeping the roots stored in human blood plasma. The AFM evaluation used 16 single-rooted human teeth embedded in resin blocks after biomechanical preparation. The samples were divided into four groups (four roots each) and the passive lateral condensation filling technique was used in the obturation of the canals with the mentioned sealers. Apexit suffered the highest degree of disintegration after the six-month storage in human blood plasma, followed by Ketac Endo and Sealapex. Sealer 26 was the most uniform cement and suffered the least disintegration.